The returns to public library investment - Gregory Gilpin; Ezra Karger; Peter Nencka (Federal Reserve Bank of Chicago, 2021)
Local governments spend over 12 billion dollars annually funding the operation of 15,000 public libraries in the United States. This funding supports widespread library use: more than 50% of Americans visit public libraries each year. But despite extensive public investment in libraries, surprisingly little research quantifies the effects of public libraries on communities and children. We use data on the near-universe of U.S. public libraries to study the effects of capital spending shocks on library resources, patron usage, student achievement, and local housing prices. We use a dynamic difference-in-difference approach to show that library capital investment increases children's attendance at library events by 18%, children's checkouts of items by 21%, and total library visits by 21%. Increases in library use translate into improved children's test scores in nearby school districts: a 1,000 or greater per-student capital investment in local public libraries increases reading test scores by 0.02 standard deviations and has no effects on math test scores. Housing prices do not change after a sharp increase in public library capital investment, suggesting that residents internalize the increased cost and improved quality of their public libraries.
Keywords: 330